Homing of radiolabelled xenogeneic equine peripheral blood-derived MSCs towards a joint lesion in a dog - Beerts, Charlotte; Pauwelyn, Glenn; Depuydt, Eva; Xu, Yangfeng; Saunders, Jimmy H.; Peremans, Kathelijne; Spaas, Jan H. (Frontiers in Veterinary Science, 2022)
Osteoarthritis (OA) is a highly prevalent condition in dogs, causing a substantial reduction in quality of life and welfare of the animals. Current disease management focusses on pain relief but does not stop the progression of the disease. Therefore, mesenchymal stem cells (MSCs) could offer a promising disease modifying alternative. However, little is known about the behavior and the mode of action of MSCs following their administration. In the current case report, 99mTechnetium labelled xenogeneic equine peripheral blood-derived MSCs were intravenously injected in a 9 year old dog suffering from a natural occurring cranial cruciate ligament rupture. The biodistribution of the MSCs was evaluated during a 6-hour follow-up period, using a full body scintigraphy imaging technique. No clinical abnormalities or ectopic tissue formations were detected throughout the study. A radiopharmaceutical uptake was present in the liver, heart, lung, spleen, kidneys and bladder of the dog. Furthermore, homing of the radiolabelled MSCs to the injured joint was observed, with 40.61 % higher uptake in the affected joint in comparison with the healthy contralateral joint. Finally, a local radioactive hotspot was seen at a part of the tail of the dog that had been injured recently. The current study is the first to confirm the homing of xenogeneic MSCs to a naturally occurring joint lesion after IV administration.